2006
DOI: 10.1590/s0074-02762006000800003
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiking Trypanosoma cruzi minicircle DNA affects gene expression in human host cells via LINE-1 retrotransposon

Abstract: Full-length RNA transcribed from the human LINE-1 (Li) element Li Homo sapiens (LlHs) has a 900-nt, G+C-rich, 5'-untranslated region (UTR). The 5' UTR is followed by two long open reading frames, ORF1 and ORF2, which are separated from each other by an inter-ORF region of 33 nt that includes two or three in-frame stop codons. We examine here the mechanism(s) by which the translation of LlHs ORF1 and ORF2 is initiated. A stable hairpin structure (AG =-74.8 kcal/mol), inserted at nt 661 of the 5' UTR, caused a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 42 publications
3
39
0
6
Order By: Relevance
“…Primary data on the integration of parasite DNA into vertebrate genomes have taken on a controversial nature [259a], with justifications that are not reasonable to many in the scientific community. The original work has been supported subsequently by additional published studies [173,366,402], of humans, rabbits, and chickens, from the authors' laboratory. After six years, the editor did not show experimental data to refute the original observations of kDNA integration.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Primary data on the integration of parasite DNA into vertebrate genomes have taken on a controversial nature [259a], with justifications that are not reasonable to many in the scientific community. The original work has been supported subsequently by additional published studies [173,366,402], of humans, rabbits, and chickens, from the authors' laboratory. After six years, the editor did not show experimental data to refute the original observations of kDNA integration.…”
Section: Introductionmentioning
confidence: 92%
“…These findings suggest that the kDNA minicircle is integrated into the macrophage genome (412). The topology of the minicircle at the integration junction site is as yet unknown, but again, the chance of two integration events occurring at a short distance favors the PCR amplification of the host DNA flanked by the kDNAs at both ends (366). In this context, the amplification of the chimeric kDNA-host DNA is obtained with primer sets annealing to the flanking kDNAs at both ends.…”
Section: Lateral Kdna Transfermentioning
confidence: 99%
“…Using this highly sensitive method, the authors identified what they interpreted as an absolute correlation between parasite persistence and tissue inflammation [16]. Simões-Barbosa et al later found evidence that the horizontal transfer of T. cruzi mitochondrial kDNA to the genomes of naturally infected humans via integration into LINE-1 retrotransposons may play an important role in the pathogenesis of CHD [17]. Although these findings have provided the strongest evidence to date that parasite persistence is crucial for the protracted progression of CHD pathology, no distinction could be made between antigens present on intact T. cruzi in the tissue and lingering T. cruzi antigens or DNA that had been shed from parasites no longer present in the proximate tissue.…”
Section: Parasite-induced Myocytolysismentioning
confidence: 99%
“…At issue was the site of integration into the vertebrate genomes. We continue to challenge our conclusions experimentally (Simões-Barbosa et al 2006), and aim to resolve any questions to the satisfaction of the scientific community. (Margulis et al 2000).…”
Section: Eons and Interplaymentioning
confidence: 97%
“…An answer to the origin of autoimmunity in Chagas disease was sought in genomic DNA from the human macrophage line U937 that had been infected (ratio 1:5) with trypomastigoes of T. cruzi (Simões-Barbosa et al 2006). All samples assayed harbored parasite DNA as judged by NAT molecular markers to T. cruzi.…”
Section: Horizontal Transfer Of Minicircle Kdna From T Cruzi To the mentioning
confidence: 99%